IMPLEMENTASI PROGRAM KELUARGA HARAPAN DI KALURAHAN SUMBERHARJO KAPANEWON PRAMBANAN KABUPATEN SLEMAN - Widianingrum, Novi; Wahyuni, Raden Roro Elisabeth Anggraeni Eksi (PARADIGMA: Jurnal Ilmu Administrasi, 2024)
The Program Keluarga Harapan (PKH) is a program providing conditional social assistance to families and/or individuals who are poor and vulnerable who are registered in the integrated data program for handling the poor, and are designated as PKH beneficiary families. Implementation of PKH is an effort made by the government to overcome the problem of poverty.Â  The research results show that the implementation of PKH in Sumberharjo according to the PKH objective indicators has been achieved well. However, the criteria indicators for PKH beneficiaries as well as the KPM rights and obligations indicators are not yet optimal, because the program targets are not yet fully on target. In the sub-indicator of receiving PKH social assistance, there are still problems in distributing aid, and in the sub-indicator of fulfilling commitments, there are still KPMs who do not fulfill their obligations to attend Group Meetings (PK) and Family Capacity Building Meetings (P2K2). Supporting factors for the implementation of PKH in Sumberharjo are that the monitoring carried out by PKH facilitators regarding the use of PKH assistance is quite good; KPM's attitude in utilizing aid is in accordance with the provisions for using aid; the role of PKH facilitators is good in providing assistance. Inhibiting factors: data on PKH recipients is less accurate, does not match conditions in the field; there are problems in the distribution of PKH assistance; KPM's lack of commitment in fulfilling its obligations; there are no sanctions for KPM who do not fulfill their commitments as PKH participants. Â Keyword: Implementation; Program Keluarga Harapan; Poverty.